EasieRR: An open‐source software for non‐invasive heart rate variability assessment. Issue 6 (17th April 2020) - Rasmussen, Jeppe Have; Rosenberger, Katrina; Langbein, Jan
Abstract: The assessment of heart rate (HR) and heart rate variability (HRV) based on electrocardiograms (ECG) is considered a good proxy for stress in a wide range of animal species. However, problems can occur e.g., when measuring ECG in ambulatory settings such as recording of unrestrained animals using non‐invasive devices. Artefacts caused by technical (i.e. bad electrode contact) or physiological (i.e. ectopic beats, non‐cardiac muscle potentials) sources are common and can disturb the ECG signal. As HRV analysis is highly sensitive to artefacts in the interbeat interval (RR‐interval) time series the process of visual inspection of the raw signal to detect and correct these is essential. Most of the commercially available software requires intensive training and extensive manual work to accomplish this task and/or is often not available to access for free. EasieRR is an open‐source, stand‐alone software optimized for analysing ECG in non‐restrained animals. The program allows a species‐specific analysis and calculation of recommended standard HRV parameters in both, the time‐ and the nonlinear domain (RMSSD, SDNN, SD1 and SD2). Visualization of data using Poincaré plots and tachograms of RR‐intervals eases the validation of correct heart cycle interval detection and minimizes manual work for the user. Automatically detected peaks can be manually corrected via deletion, correction of spurious detections or marking of undetected peaks. The HRV analysis can be exported using common formats (TXT, MAT). Figures can be plotted and exported in various formats (PDF, SVG, PNG, JPG, TIFF, EMF and EPS). Included in EasieRR is the possibility for synchronization of ECG data with video in order to link cardiac responses to specific behavioural responses. Zusammenfassung: Die Analyse der Herzfrequenz (HF) und der Herzfrequenzvariabilität (HRV) aufgrund von Elektrokardiogrammen (EKG) kann zur Evaluation von Stress bei Tieren herangezogen werden. Fehlerhafter Hautkontakt der Messtechnik und Muskelpotentiale durch Bewegung können zu Artefakten im EKG und in Folge zu Fehlern im Tachogramm führen. Die visuelle Inspektion des EKG und eine anschließende Korrektur falsch detektierter QRS‐Komplexe ist daher unerlässlich, kann jedoch mit verfügbarer Software einen zeitaufwendigen Prozess darstellen. EasieRR ist eine benutzerfreundliche und frei‐zugängliche Software optimiert zur EKG‐Analyse am Tier. Das Programm ermöglich eine Art‐spezifische Analyse im zeitbasierten (mittlere HF, SD, RMSSD) und nicht‐linearen Bereich (SD1, SD2). Die Benutzeroberfläche von EasieRR kombiniert EKG und Tachogramm mit der Darstellung von Poincaré‐Plots und erleichtert somit das Auffinden von Artefakten, deren Korrektur und die HRV Analyse. Während der visuellen Inspektion als fehlerhaft erkannte R‐Zacken können manuell gelöscht, verschoben oder neu eingefügt werden. Die Ergebnisse der HRV‐Analyse können in gängigen Formaten (MAT, XLSX) exportiert werden und stehen für weitere statistische Anwendungen zur Verfügung. Grafiken können im Format PDF, SVG, PNG, JPG, TIFF, EMF und EPS gesichert werden. EasieRR ermöglich auch die Synchronisation von Videoaufnahmen mit EKG‐Daten, und somit die Verknüpfung von Herzfrequenzparametern mit spezifischen Verhaltensweisen.